2010
DOI: 10.4155/tde.10.13
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-assisted Combination Therapies for Effective Cancer Treatment

Abstract: Combination chemotherapy and nanoparticle drug delivery are two areas that have shown significant promise in cancer treatment. Combined therapy of two or more drugs promotes synergism among the different drugs against cancer cells and suppresses drug resistance through distinct mechanisms of action. Nanoparticle drug delivery, on the other hand, enhances therapeutic effectiveness and reduces side effects of the drug payloads by improving their pharmacokinetics. These two active research fields have been recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
333
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 512 publications
(348 citation statements)
references
References 69 publications
3
333
0
1
Order By: Relevance
“…showing that combined polymersome-delivered therapy is much better than single drug encapsulated therapy. The effect of combinational therapy, delivered via nanoparticles, has been extensively reviewed and current evidence shows that this combinational therapy is highly dependent on the molar ratios of drugs and the sequence in which they are delivered 43 . In support of this, we observed that the cytotoxicity of dual loaded polymersomes is greater than polymersomes loaded with a single drug.…”
Section: Cellular Internalisation Kineticsmentioning
confidence: 99%
“…showing that combined polymersome-delivered therapy is much better than single drug encapsulated therapy. The effect of combinational therapy, delivered via nanoparticles, has been extensively reviewed and current evidence shows that this combinational therapy is highly dependent on the molar ratios of drugs and the sequence in which they are delivered 43 . In support of this, we observed that the cytotoxicity of dual loaded polymersomes is greater than polymersomes loaded with a single drug.…”
Section: Cellular Internalisation Kineticsmentioning
confidence: 99%
“…Current aggressive multidisciplinary advances in improving the efficacy of cancer therapeutics are due to combination of these two dynamic research fields (Mollazade et al, 2013). There are also some challenges and design specifications that need to be addressed in optimizing nanoparticle-based combination chemotherapy (Kalaria et al, 2009;Guhagarkar et al, 2010;Hu et al, 2010;Benival and PV, 2012;Jain et al, 2012;Deng and Zhang, 2013;Duong and Yung, 2013;Liboiron and Mayer 2014;Salehi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, combination therapy uses combined regimes that multiply the additive effects to the targeted cancer cells (Tacar et al, 2013). Afterwards, when synergistic combination with enhanced therapeutic effects get combined with an appropriate nanodelivery system such as the nanoparticles, a much powerful anticancer weapon create that could efficiently and specifically target tumoral cells (Yoo and Park, 2004;Hu et al, 2010;Wang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Combination chemotherapy and nanoparticle drug delivery put forwards significant promise in cancer treatment. Concomitant use of two or more drugs results in additive\synergic cytotoxic on cancer cells and can overcome drug resistance through distinct mechanisms of action (Hu et al, 2010;Rossi et al, 2010). On the other side, nanoparticle drug delivery enhances therapeutic effectiveness whilst reduces toxicity on healthy cells through improving their pharmacokinetics.…”
Section: New Formulated "Dox-mtx-loaded Nanoparticles" Downregulate Hmentioning
confidence: 99%